Commentaries on Marketing Systems - Desai, Gunvant M.; Falusi, Abiodun O.; Schluter, Michael; Gapare, Robinson L. (International Food Policy Research Institute, 1987)
Poor agricultural growth in sub-Saharan Africa is sometimes attributed to the absence of major technological breakthroughs suited to its agroclimatic environment. This implies that there is little room for growth in agricultural production in the existing technological environment. Viewed in this way, development of superior technologies becomes the most important issue in policies for accelerating agricultural growth in sub-Saharan Africa. Without belittling the importance of improved technology, the two chapters under discussion caution against this position.